Asymptomatic Carriage of C. botulinum Type D/C in Broiler Flocks as the Source of Contamination of a Massive Botulism Outbreak on a Dairy Cattle Farm - Souillard, Rozenn; Grosjean, Daniel; Le Gratiet, Thibault; Poezevara, Typhaine; Rouxel, Sandra; Balaine, Loïc; Macé, Sabrina; Martin, Laure; Anniballi, Fabrizio; Chemaly, Marianne; Le Bouquin, Sophie; Le Maréchal, Caroline (Frontiers in Microbiology, 2021)
In winter 2018, a massive type D/C cattle botulism outbreak occurred on a mixed dairy and broiler farm in France. An investigation was conducted based on the hypothesis of asymptomatic carriage in poultry. We set out to identify the source of contamination of the dairy cattle and to monitor the contamination of broilers over time, including the hatchery delivering chicks to the farm. Environmental samples were collected on the farm during the cattle outbreak (n=40), after the outbreak for three successive broiler flocks (n=128) and once in the hatchery delivering the chicks (n=58). These samples were analyzed using real-time PCR after an enrichment step to detect Clostridium botulinum type D/C. The results showed contamination in the manure from the broilers raised just before the onset of the cattle outbreak (5+/5), as well as in some of the components of the cattle ration (3+/17). This latter contamination is likely due to the use of the same tractor bucket to remove litter from the poultry house and to prepare the cattle ration on the same day. Contamination monitoring over several months revealed continuous asymptomatic carriage in the broilers (4+/20 and 17+/20 cloacal swabs in 2 successive flocks), a persistence of C. botulinum type D/C in the ventilation system of the poultry house (8+/14), and contamination of the equipment coming from the hatchery used for delivering the chicks (3+/18). Further investigations conducted in the hatchery demonstrated contamination in the hatchery by C. botulinum type D/C (6+/58). Comparison of samples using a multilocus variable number tandem repeat analysis showed the same profile for samples collected on broilers, cattle and in the hatchery. This study highlighted the crucial role of the implementation of biosecurity measures in mixed farms to avoid cross-contamination between production units given the potential asymptomatic carriage of poultry. This study also revealed the contamination of the poultry hatchery. Further investigations are required to better understand the role of hatcheries in the epidemiology of animal botulism.